New approach to seismic-resistant design and structural torsion mitigation. (15th March 2020) - Ismail, Mohammed
Highlights: New approach to seismic-resistant design of structures is proposed and investigated. The proposal provides the advantages of seismic isolation and energy dissipation. The proposal is a new, multi-feature, economic seismic-resistant design approach. It is applicable to short- & long-period structures; new & existing constructions. The proposal mitigated significantly the structural responses including torsion. Abstract: A new approach to seismic-resistant design of structures and mitigation of structural torsion is introduced and investigated. It is based on the controlled adaptation of all the structural columns of a single storey to partially decouple the superstructure from the moving ground. In addition, it allows to maintain adequate vertical rigidity together with adding notable horizontal flexibility; reduces storey drift; provides a resistance to lateral loads and to minor vibration; generates a self-restoring mechanism; incorporates a self-stopping mechanism besides ensuring the structural stability under extremely severe earthquakes. The new approach is not intended to form any plastic hinges or rely on them to provide damping, therefore, supplementary damping is provided using a new displacement-based bracing system designed by the author. A set of multi-storey asymmetric structures of 6- to 16-storey are considered to numerically assess the proposal's efficiency under near-fault and long-period earthworks. Using nonlinear time history analysis, the 3D structures are examined under unidirectional ground motions applied along the most unfavourable horizontal direction, to produce the worst torsional responses that are to be mitigated using the new approach. It was found that the new approach has reduced significantly the structural responses including torsion. The base storey was found the optimum level for applying the new approach to ensure the highest efficiency. Furthermore, it was found that the proposed approach provides all the advantages of seismic isolation plus an additional benefit, that is, the new proposal is suitable for both short- and long-period structures. Simultaneously, the new proposal provides all the good characteristics of supplemental energy dissipation, plus an extra function, as it reduces inter-story drift, additionally.